Przerzuty raka sutka do skóry – różne obrazy kliniczne - Pekmezci, Erkin; Küçükodacı, Zafer; Kutlubay, Zekayi (Dermatology Review/Przegląd Dermatologiczny, 2021)
Cutaneous metastases usually appear as non-specific groups of discrete, firm, painless nodules that emerge rapidly without any explanation. Some skin metastases may mimic specific dermatological conditions such as cutaneous cysts, dermatofibroma, granuloma teleangiectodes, hemangioma, herpes zoster eruptions, rapidly infiltrating plaques, alopecic patches, erysipelas and cellulitis [1].